The effect of ultrasonication temperature on snakehead fish (Channa striata) dispersion. Issue 1 (April 2020) - Rahmaniar; Dirpan, A; Mahendradatta, M; Asfar, M; Tawali, A B
Abstract: Dispersion of snakehead fish ( Channa striata ) is one of the development products from the supplement of snakehead fish. It is made for people who cannot consume supplements in pill form. The dispersion of snakehead fish that have been made before having a large particle size so that it was unstable. This research aimed to study the effect of ultrasonication temperature on snakehead fish dispersion. The making of snakehead fish dispersion was carried out with the ultrasonication method by Powersonic 405 frequency 40kHz for 60 minutes with temperature treatment of 30°C, 45°C, and 60°C respectively. The result shows that the temperature of ultrasonication has the effect of the ratio of phase separation and an increase in total dissolved solids.